2007
DOI: 10.1111/j.1399-6576.2006.01225.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement properties of the Short Form 36 and health‐related quality of life after intensive care in Morocco

Abstract: The Arabic version of the SF-36 appears to be a robust tool in ICU. Background variables are the only significant determinants of HRQL 3 months after medical ICU discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 35 publications
(53 reference statements)
6
59
0
2
Order By: Relevance
“…[65][66][67][68]70,72,73,[75][76][77][78][79] Similar to previous research, the Social Functioning scale had the poorest internal consistency (Tab. 1).…”
Section: Sf-36supporting
confidence: 57%
See 1 more Smart Citation
“…[65][66][67][68]70,72,73,[75][76][77][78][79] Similar to previous research, the Social Functioning scale had the poorest internal consistency (Tab. 1).…”
Section: Sf-36supporting
confidence: 57%
“…79 The time interval between tests in these studies often was 2 weeks. 64,65,67,69,71,73,75,76,78,79 Other time intervals used were 4 weeks, 72 3 weeks, 68 1 week, 66,70,73,74,77 and 2 days. 63,71 Fourteen studies 63-65,68 -76,78,79 were selfadministered with either paper or a computer, 2 studies 66,67 were administered via telephone or personal interview, and 1 study 77 …”
Section: Sf-36mentioning
confidence: 99%
“…The SF-36 score distribution in the current study is similar to those reported by Khoudri et al who evaluated the Arabic version at three months post-ICU discharge (17). They described that the discriminant validity was good and concluded that the Arabic version of SF-36 was a robust tool in ICU.…”
Section: Discussionsupporting
confidence: 76%
“…Reliability was estimated using the internal consistency method and test-retest method 23,24) . Validity was assessed using convergent and discriminant validity checks 25,26) .…”
Section: Discussionmentioning
confidence: 99%